Classification of English and Armenian age units according to age scales - Adamyan, Mariam (Bulletin of Yerevan University B: Philology, 2021)
The category of time, ideas about it, have various forms of representation in human life. One of these forms can be the category of age․ Each ethnic culture has traditional age groups that may differ from culture to culture. The work represents the classification of age units of the English and Armenian languages in accordance with the general age scales of the mentioned linguistic cultures.